composition of functions
Thank you for the opportunity to help you with your question!
f(x) = 3x + 4 and g(x) = 7x -9
go f (x) = g [f)x)] = g (3x + 4)
= 7 (3x + 4) -9 [ replace x by 3x + 4 in the formula for g(x)]
= 21x + 28 -9
= 21 x + 19
Note if f(x) = 3x-4 then gof (x) = = 7 (3x - 4) -9 [ replace x by 3x - 4 in the formula for g(x)]
= 21x -28 -9
= 21 x - 37
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?